Editorial: colorectal cancer in elderly‐onset inflammatory bowel disease—what is the risk?. Issue 9 (11th October 2022) - Weiss, Alexandra; Buchner, Anna M.
Abstract : LINKED CONTENT This article is linked to Everhov et al papers. To view these articles, visit https://doi.org/10.1111/apt.17175 and https://doi.org/10.1111/apt.17229